Practice standard for project estimating (Project Management Institute, Inc., 2011)
Presents guidelines for project managers on developing costs, resources, and time estimates in the early stages of a project and techniques for refining these estimates during each project stage.
Keywords: Project management -- Estimates.; Project management -- Standards.; Cost control.; elektronické knihy; electronic books